Bridge Duty On A Ship: Study On Preventing Collisions At Sea On The Training Ship John Lie - Haryadi Wijaya; Hadi Setiawan (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
The knowledge and skills of a ship's crew can play a key role in preventing collisions. The Bridge Watchkeeping Duty becomes crucial in this context, as they are the first to detect potential threats. Given the increasing risks in maritime transportation and the need to prevent ship collisions, several steps can be taken. One of them is to effectively carry out the tasks and functions of the Bridge Watchkeeping Duty. Therefore, this study aims to analyze the Bridge Watchkeeping Duty, specifically, the efforts to prevent sea collisions conducted by the Ship's Bridge Watchkeeping Service, and how its theoretical and practical implementation is carried out in the field. This qualitative study uses a descriptive method to describe and elaborate on the study object, namely the John Lie training ship. The study will include quotations from various data sources such as interviews, field notes, memos, and other official documents. Data analysis in this study uses the techniques of Miles and Huberman. The results of this study indicate that the implementation of these duties and responsibilities must always be based on a deep understanding of various national and international maritime regulations, as well as knowledge of the characteristics of the ship and its surrounding environment. Additionally, implementing regulations such as the 2010 Manila Amendments to the STCW 2010 is also important to ensure the welfare and fitness of the watchkeepers so they can perform their duties and responsibilities optimally. This study has several limitations, such as variables that need to be explored further, such as the psychological aspects of bridge watchkeepers who bear a heavy workload, extreme sea weather conditions, and ship facilities that support collision prevention activities. Thus, this study is expected to provide constructive thoughts and suggestions for maritime transportation stakeholders, particularly sailors and crew members, regarding the importance of properly implementing the Bridge Watchkeeping Duty. Focus on the human aspect in preventing ship collisions at sea through the Ship's Bridge Watchkeeping Service.